Cost of an elaborate trait: a trade-off between attracting females and maintaining a clean ornament. (4th August 2020) - McCullough, Erin L; Chou, Chun-Chia; Backwell, Patricia R Y
Abstract: Many sexually selected ornaments and weapons are elaborations of an animal's outer body surface, including long feathers, colorful skin, and rigid outgrowths. The time and energy required to keep these traits clean, attractive, and in good condition for signaling may represent an important but understudied cost of bearing a sexually selected trait. Male fiddler crabs possess an enlarged and brightly colored claw that is used both as a weapon to fight with rival males and also as an ornament to court females. Here, we demonstrate that males benefit from grooming because females prefer males with clean claws over dirty claws but also that the time spent grooming detracts from the amount of time available for courting females. Males, therefore, face a temporal trade-off between attracting the attention of females and maintaining a clean claw. Our study provides rare evidence of the importance of grooming for mediating sexual interactions in an invertebrate, indicating that sexual selection has likely shaped the evolution of self-maintenance behaviors across a broad range of taxa. Abstract : Grooming is important for male fiddler crabs. Males court females by waving a big, colorful claw and groom frequently to keep their claw clean. Females find males with clean claws more attractive than males with dirty claws, but the time spent grooming reduces the time available for waving. Males, therefore, face a trade-off between being clean and attractive and catching the attention of females. Even in fiddler crabs, there are costs to staying beautiful.